(untitled) (Our Nature, 2018)
Tinjure-Milke-Jaljale (TMJ) Conservation Area (Lat. 27°6ʹ57ʺ-27°30ʹ28ʺ N, Long. 87°19ʹ46ʺ -87°38ʹ14ʺ E; alt. 1700-5000 m; area 585.26 km2) lies between Arun and Tamor rivers in eastern Nepal. This area is popular for Rhododendron, the national flower of Nepal, and has been recognized by “The capital of Rhododendron”.